Theosophy across boundaries: transcultural and interdisciplinary perspectives on a modern esoteric movement - Strube, Julian; Krämer, Hans Martin (State University of New York Press, 2020)
"Demonstrates that Theosophy was part of a truly global movement and played an important role in the general histories of religion, science, philosophy, art, and politics"--
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Interdisziplinäre Forschung; Religionswissenschaft; Einfluss; Esoterik; Theosophie